Review and analysis of clinical trials of selective RET inhibitors for the treatment of thyroid cancer - Zhou, Yulu; Cao, Junjie; Zhang, Siqi; Sun, Mingjun; Zhang, Yaqi; Li, Songzhe; Luo, Zining; Wang, Pengyu; Xie, Jiebin (Frontiers in Oncology, 2025)
The global incidence of thyroid cancer has increased significantly, and patients with advanced, recurrent, or radioiodine-refractory disease face a severe shortage of effective treatment options. The RET proto-oncogene serves as a key driver in the development of thyroid cancer, and its alterations are closely associated with highly aggressive tumor subtypes. Although the emergence of highly selective RET inhibitors (such as selpercatinib and pralsetinib) has revolutionized the treatment landscape, their complete clinical development pathway, rational combination strategies, and future research priorities still require systematic clarification. Understanding the development trends of these drugs is important for guiding clinical decision-making, optimizing trial design, and accelerating new drug development. We searched 16 clinical trial registries, and identified 18 studies registered up to 21 March 2025. Our analysis revealed that among the 18 eligible trials, the majority were Phase 1/2 studies. Selpercatinib and pralsetinib are the most frequently studied RET inhibitors. Notably, research on next-generation RET inhibitors as monotherapy approaches (e.g., LOXO-260, enbezotinib, SY-5007 and TY-1091) is currently underway. Additionally, combination regimens incorporating these inhibitors with agents such as ¹³¹I, recombinant human thyroid-stimulating hormone (rhTSH), and anti-programmed cell death protein 1 (anti-PD-1) antibodies are becoming an increasingly important area of investigation. While selective RET inhibitors have demonstrated therapeutic potential, concerns regarding drug resistance and toxicity persist. Therefore, future strategies should prioritize the development of next-generation inhibitors and the optimization of combination regimens to improve outcomes for RET-altered thyroid cancer patients.